The Effect Of Institutional Ownership, Profitability, Leverage, And Free Cash Flow On Earnings Management In Banking Companies Listed On The Indonesian Stock Exchange (Idx) From 2018 To 2023 - Dinal Eka Pertiwi; Ahmad Junaidi; Desi Fitria; Theo Alanthre Kevin (UNIVED Press, 2026)
Information about profits is very important for interested parties. Some parties await this information for various reasons. Both internal and external parties need this profit information for financial statement analysis in order to make decisions. Therefore, profits are closely watched by various parties such as investors, creditors, employees, and accounting policy makers. This study aims to examine the influence of Institutional Ownership, Profitability, Leverage, and Free Cash Flow on Profit Management in Banking Companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2023. This study employs a quantitative method using secondary data, namely company financial statements from the Indonesia Stock Exchange (IDX) via the website www.idx.co.id or the company's official website. The population in this study consists of banking companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023. The sample was selected using purposive sampling, resulting in 30 companies that met the criteria, yielding 180 observations. Data analysis was conducted using multiple linear regression analysis with the assistance of SPSS 26. The results of the study indicate that Institutional Ownership does not affect Profit Management, as seen from the t-value of 0.200 and the sig value of 0.842 > 0.05. Profitability affects Profit Management, as seen from the t-value of 2.470 and the sig value of 0.015 > 0.05. Leverage has no effect on earnings management, as seen from the t-value of -1.178 and a significance value of 0.241 > 0.05. Free cash flow affects earnings management, as seen from the t-value of -18.718 and a significance value of 0.000. Institutional ownership, profitability, leverage, and free cash flow simultaneously affect earnings management, as seen from the calculated F value of 74.768 with a significance level of 0.000 or less than 0.05.